Textbook of autism spectrum disorders - Hollander, Eric, 1957-; Hagerman, Randi Jenssen, 1949-; Ferretti, Casara Jean (American Psychiatric Association Publishing, 2022)
"More than 40 years after the official recognition of infantile autism in DSM-III, advances continue to be made in our understanding of the possible causes, assessment and evaluation, and treatment of autism spectrum disorder (ASD). With contributions by dozens of experts in the field, this second edition of the Textbook of Autism Spectrum Disorders has been updated to reflect the latest research in ASD. Unrivaled in its thoroughness, this volume discusses issues of assessment and evaluation; examines the etiology of ASD and its recognized associations with other medical conditions; analyzes standard and experimental treatments; and delves into social policy issues pertinent to individuals with ASD and those who treat them. With summary points in each chapter and copious lists of recommended readings, this is an indispensable resource for psychiatrists, psychologists, neurologists, social workers, speech therapists, educators, and all others in the continuum of care"--